Assessing the role of dynamic capabilities in local food distribution: a theory-elaboration study. Issue 6 (26th September 2019) - Gruchmann, Tim; Seuring, Stefan; Petljak, Kristina
Abstract : Purpose: The food industry and its distribution solutions often lie at the center of sustainability-related arguments. However, little is known about the dynamic role of business capabilities for sustainable transformations in the context of local food distribution. Accordingly, this study aims to investigate how dynamic capabilities drive sustainable supply chain management (SSCM) business practices in short food supply chains (SFSCs) through the professionalization and expansion of online distribution channels. Design/methodology/approach: The present study analyzes sustainability-related practices at six online distribution channels selling local food products in Germany and Austria. By applying a cross-case study and theory-elaboration approach, the study analyzes empirical data derived from these businesses and provides insights into how dynamic capabilities can facilitate SSCM practices within SFSCs. Hereby, potential pathways for a sustainable transformation in this industry context are deduced through abductive reasoning. Findings: The empirical findings provide evidence that supply chain orientation, coordination, innovation practices and strategies are highly relevant for SFSCs seeking to reach upscaling effects in regional markets. However, because SFSCs may not be able to reach mass markets without weakening their own sustainability performance, the present study recommends addressing sustainability inefficiencies in the region and developing further expansion potentials through replication in other regions. In this approach, related and necessary SSCM dynamic capabilities were identified and validated based on the empirical findings. Originality/value: Although SFSCs include sustainability aspects at their core – particularly regarding resource usage, environmental friendliness and social-standard assurance – missing distribution-related capabilities limit growth such that these businesses often remain in a niche. To address this issue, the study builds on dynamic capabilities theory by identifying and describing core SSCM practices and capabilities; moreover, this study is among the first to elaborate empirically on the use of dynamic capabilities theory in this specific industry context.